THE EFFECT OF FREQUENCY VARIATION ON DIELECTRIC CONSTANT OF RAPHIA HOOKERI - Ubong Iboh; Ubong Robert; Grace Umoren; Uduakobong Okorie (Journal of Renewable Energy and Mechanics, 2020)
This work sought to investigate the effect of varying the frequency of an applied electric field on the dielectric constant of raphia hookeri. The aim of the work was to ascertain the suitability of using the sample for engineering applications. It was revealed, from the recorded results, that the dielectric constant of the sample decays exponentially with frequency. Also, greater degree of polarisation was observed with decrease in frequency. Again, as a good thermal insulator, it was revealed that the values of the sample’s dielectric constant compared favourably with those of commonly used conventional dielectric materials. Thus, it is obvious that if put into production cycle, the sample can serve as a low-cost and environmentally friendly material suitable for engineering applications within audio frequency range. This will, in turn, help to provide raw material for electronic industry and also improve the economy.